Gender contribution to the innovation-productivity relationship in the wake of COVID-19: Evidence for the Caribbean - Ezequiel Tacsir; Mariano Pereira (Inter-American Development Bank (IDB), 2023)
This study presents new findings on the impact of the COVID-19 pandemic on productivity and innovation for Caribbean firms, with particular focus on the effects on firm gender diversity and workforce composition. Research on the impact of women's participation on firm performance and innovation has so far produced mixed results, though there is some evidence to suggest that for Latin America, larger shares of women in the knowledge creation and innovation process may increase innovative behavior and, as a consequence, lead to greater labor productivity. In the current context, female participation in firms becomes an even more pressing issue, given the early indications of the pandemics disproportionately negative burden on women s income and jobs in different regions. We found that the gender composition of the personnel has an interesting direct effect on productivity. At the same time, our results show that the expected reductions in female personnel due to the pandemic, have a negative effect in the shares of female participation which, in turn, have the potential to nullify the mentioned productivity channel. This suggests the existence of a minimum threshold of female participation to profit from diversity. Hence, it seems that policy should focus particularly on protecting female jobs, particularly in the wake of dramatic shocks affecting revenues and/or employment.
Keywords: O32; J16; D22; 330; Caribbean; pandemic; innovation; gender; productivity